ANALYSIS OF ACCOUNTS RECEIVABLE TURNOVER AT PT. XXY, A MANUFACTURING COMPANY IN GRESIK - Febriyanti, Berliana; Reviandani, Wasti; Vilantika, Elok (Komitmen: Jurnal Ilmiah Manajemen, 2024)
This research aims to analyze the accounts receivable turnover at PT. XXY, a manufacturing company in Gresik. The study focuses on the efficiency of the company's receivables management in measuring how quickly the company converts trade receivables into cash. The analytical method involves collecting historical data on receivables, financial statements, and the company's receivables management policies. The research results will provide in-depth insights into the effectiveness of the company's receivables policies and offer recommendations to enhance accounts receivable turnover. This study has strategic implications for improving the company's liquidity, optimizing financial resources, and supporting sustainable growth. Thus, the research makes a significant contribution to both practical and academic understanding of financial management in manufacturing companies.